Utilization of Maternal and Child Health Services among Women Admitted In Maternity Ward of A Hospital of Siddharthanagar Municipality - Khatri, Binita; Grurung, Saraj; Kachapati, Anuja (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION Maternal and child mortality is a global issue which could be prevented by the utilization of maternal and child health (MCH) services. The main objective of this study was to find out the utilization of MCH services among women admitted in maternity ward of a hospital. MATERIAL AND METHODS Cross-sectional descriptive study was conducted to find out the utilization of MCH services among 150 women admitted in maternity ward of a hospital. Non-probability purposive sampling technique was used to select the sample and semi- structured interview schedule was used to collect the data and collected data was analyzed with SPSS version 16. RESULTS The study showed that 100% of the women had utilized antenatal services, 98.67% delivered their baby in health centres and utilized postnatal services. During pregnancy, women got health education on danger signs (66.67%), avoidance of sexual intercourse (54%), and birth preparedness (44%). Cent percent of the children utilized at least one child health services, 80% were breastfed within hour of birth, and 93.24% of women were not aware of administration of vitamin K to their newborn. Ethnicity, religion, education, occupation, age at marriage, gravida, parity, history of abortion or child death and number of live children of women, education and occupation of spouses were significantly associated (p<0.05) with utilization of maternal health services. CONCLUSION It is recommended that nurses and health personnel should provide health education focusing on birth preparedness, danger signs of mother and baby, and should inform about administration of vitamin K to mother.